Energy Poverty, Practice, and Policy - Butler, Catherine (Progressive Energy Policy, 2022)
"Catherine Butler's new book is theoretically innovative, bringing much-needed insights on poverty and vulnerability into the study of Social Practices. It offers in-depth analysis of how "invisible energy policies" operate in the real world, revealing the important intersections between welfare policies and energy in everyday life. Amid the cost of living crisis, and the ever-more contested politics of social security, this book makes a hugely timely contribution, and will be a valuable resource for researchers, students, and all those concerned with understanding and promoting energy justice." -Sarah Royston, Anglia Ruskin University, UK This Open Access book examines the implications of welfare policy for energy poverty and engages with key conceptual debates at the forefront of energy demand research. Academic work on energy poverty has rarely been brought into conversation with practice-theory-based approaches to energy use and sustainability. This book reveals how novel insights can be made visible through combining these different ways of thinking about energy demand issues. It presents a distinctive approach to energy poverty that places inequalities at the heart of debates about the advancing energy intensity of contemporary societies. Dr Catherine Butler is Senior Lecturer in Human Geography at University of Exeter. Her research centres around analysis of environmental governance processes with focus on the intersections between policy, politics, and everyday life. She has published extensively on topics including energy transitions in everyday life, behavioural change and social practice, wellbeing impacts of environmental change processes, and governance of climate adaptation. This book arises out of her four-year EPSRC (Engineering and Physical Sciences Research Council) funded project. .